Role of platelet-rich plasma: The current trend and evidence - Kailash Kothari (Indian Journal of Pain, 2017)
Platelets contain many important growth factors, which helps in healing. These lead researchers to inject high concentration of Platelets in plasma (platelet-rich plasma [PRP]) at injury site. There is a variety of PRP preparations produced by the different commercial equipment. The concentration of platelets should be more than 5 times the normal in PRP. PRP can be used for long list of conditions, for example, orthopedic, neurology, musculoskeletal, cardiology, dermatology, and plastic surgery. The research on PRP is still in infancy, and there is no consensus on platelet concentration, amount of PRP, which is the best technology in preparing PRP. There are many animal studies, which are showing encouraging results, but human studies are lacking. PRP is very promising treatment option which is nonsurgical. We need to wait for more concrete evidence to emerge to define its exact clinical role.